2021
DOI: 10.1159/000516473
|View full text |Cite
|
Sign up to set email alerts
|

The Saudi Experience of Health-Related Social Media Use: A Scoping Review

Abstract: <b><i>Objectives:</i></b> Social media (SM) are evolving and dynamic applications which can be used in health-care settings to enhance professional networking and education; patient communication, care, and education; public health programs; organizational promotion; and research. This review aims to analyze, summarize, and describe the current Saudi experience of SM use for health. <b><i>Methods:</i></b> A MEDLINE/PubMed electronic database search was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…The implementation of telemedicine, however, has encountered various barriers in Saudi Arabia. These issues include bureaucracy, lack of expertise, inadequate IT infrastructure, absence of guidelines, and insufficient institutional support [ 9 ]. Therefore, Saudi Arabia’s Ministry of Health must assess health care workers’ knowledge and perceptions of telemedicine to facilitate its future implementation while considering patient privacy and confidentiality concerns [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of telemedicine, however, has encountered various barriers in Saudi Arabia. These issues include bureaucracy, lack of expertise, inadequate IT infrastructure, absence of guidelines, and insufficient institutional support [ 9 ]. Therefore, Saudi Arabia’s Ministry of Health must assess health care workers’ knowledge and perceptions of telemedicine to facilitate its future implementation while considering patient privacy and confidentiality concerns [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through technological advancements and appropriately oriented policy developments, telemedicine could become a sustainable mainstream solution for both public health emergencies and routine care [ 9 ]. Telemedicine may be a reasonable choice for physicians in the future if properly used by patients and if legal guidelines for telemedicine are implemented to address the aforementioned concerns [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Screening of the literature revealed that the average search for health information by Saudis via the internet and social media varies from 50% to 90%. 7,12,19,20 In these studies, Twitter was the most used social media platform among Saudi adults to search for health information due to the ease of performing the search. These results are consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…10 Similarly, these participants perceived nutritional information from both healthcare professionals and online sources to be very reliable. 10 Research studies from different countries (USA, Australia, and Saudi Arabia) stated the use of several social media platforms in aspects related to health 6,[11][12][13] ; however, no investigation has examined the use of social media to search for weight loss information among Saudis. The objectives of the current study were to assess the prevalence and patterns of using social media as a source for weight loss information among Saudi adults and to assess their perceptions of the benefits and risks related to this practice.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the bulk of the scientific literature on telemedicine use focuses on topics such as its usability, costeffectiveness [5,[10][11][12], platforms used, user characteristics [10,13], application challenges and facilitators [14], and patient and physician satisfaction [15][16][17]. When dedicating the search to the ethical and legal aspects of telemedicine, these were not as thoroughly covered, with a very limited assessment of related real-life experiences of healthcare practitioners, their perspectives and attitudes, particularly in Arab countries [18,19].…”
Section: Introductionmentioning
confidence: 99%